522 nm single-longitudinal-mode high-frequency Pr3+:YLF laser based on pre-lase Q-switching technology. (1st July 2022) - Jiang, Meng; Jin, Long; Liu, Chang; Dong, Yuan; Jin, Guang-yong
Abstract: In this work, based on the pre-lase Q-swiching technology, a single-longitudinal-mode (SLM) pulsed laser that can be emitted directly into the green spectral region at 522 nm is demonstrated for the first time. The rate equation of 522 nm Pr 3+ :YLF SLM Q-switched laser is established, and the output characteristics of the laser are obtained by simulation. The peak power of 37.9 W was obtained under an incident pump power of 12 W at 444 nm. At a repetition frequency of 20 kHz, the laser pulse energy and the pulse width were measured to be 3.05 μ J and 80.5 ns, respectively. The corresponding spectral linewidth is approximately 22 MHz.